A Vocational Student Service Information System Using Mobile Technology - Wahyudi, Muhammad Dedi (Journal of Computer Science Application and Engineering (JOSAPEN), 2023)
Education's purpose at Vocational High School (SMK) PGRI 3 Palembang emphasizes holistic student development, encompassing religious, intellectual, and character aspects. With a significant student body, manual administrative processes hinder effective discipline enforcement and extracurricular management. To address these issues, a mobile-based student information system is proposed to expedite disciplinary actions, attendance tracking, and extracurricular selections. Employing the waterfall model, the study progresses through phases of system development, culminating in the design and testing of a robust system architecture. Utilizing UML diagrams, the system is outlined, featuring actors such as administrators, teachers, and the deputy principal. The client-server model, with a mobile app and web server, facilitates efficient data management and presentation. Black box testing confirmed the system's operational efficacy. This proposed system offers a comprehensive solution to streamline administrative tasks, enhancing decision-making and operational efficiency at SMK PGRI 3 Palembang.